Two Patients With KCNT1-Related Epilepsy Responding to Phenobarbital and Potassium Bromide. (October 2019) - Datta, Anita N.; Michoulas, Aspasia; Guella, Ilaria; ,; Demos, Michelle
KCNT1 encodes a sodium-activated potassium channel highly expressed in the brain, regulating hyperpolarization following repetitive firing. Mutations in KCNT1 were originally implicated in autosomal-dominant nocturnal frontal lobe epilepsy and epilepsy of infancy with migrating focal seizures. It is now known that there is variability in phenotypic expression and incomplete penetrance. We describe 2 patients with KCNT1 -related epilepsy, one with epilepsy of infancy with migrating focal seizures and one with multifocal epilepsy. As most patients with KCNT1 variants have treatment-resistant epilepsy, drugs that specifically target the KCNT1 channel have been of great interest. Quinidine, a broad-spectrum potassium channel blocker, has shown promise; however, clinical trial results have been variable. Our patient with epilepsy of infancy with migrating focal seizures did not respond to a trial of quinidine at 6 weeks of age—one of the earliest reported quinidine trials in the literature for KCNT1 -related epilepsy. This indicates that timing of treatment and response may not be related. Both patients responded to high-dose phenobarbital. The patient with epilepsy of infancy with migrating focal seizures also had a significant reduction in seizures with potassium bromide (KBr). Our data suggest that alternative therapies to quinidine should be considered as a therapeutic option for patients with KCNT1 -related epilepsy. Although improved seizure control led to parent-reported improvements in neurodevelopment, it is unknown if phenobarbital and KBr impact the overall developmental trajectory of patients with KCNT1 -related epilepsy. Further multicenter longitudinal studies are required.